2020
DOI: 10.1109/access.2020.2991263
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Graph Convolutional Network-Based Multi-Task Transient Stability Assessment Framework in Power System

Abstract: Reliable online transient stability assessment (TSA) is fundamentally required for power system operation security. Compared with time-costly classical digital simulation methods, data-driven deep learning (DL) methods provide a promising technique to build a TSA model. However, general DL models show poor adaptability to the variation of power system topology. In this paper, we propose a new graphbased framework, which is termed as recurrent graph convolutional network based multi-task TSA (RGCN-MT-TSA). Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 37 publications
(39 reference statements)
0
21
0
Order By: Relevance
“…Although this study mainly focuses on deriving distribution characteristics of power flows, the main methodology can be further used for anomaly detection in the future. Moreover, the work [109] integrates GCN with long short-term memory (LSTM) network to construct the recurrent graph convolutional network (RGCN). Experiments on both IEEE 39 Bus and IEEE 300 Bus system verify the effectiveness of the proposed RGCN model for collective anomaly detection so as to ensure the stability of power grids.…”
Section: Collectivementioning
confidence: 99%
“…Although this study mainly focuses on deriving distribution characteristics of power flows, the main methodology can be further used for anomaly detection in the future. Moreover, the work [109] integrates GCN with long short-term memory (LSTM) network to construct the recurrent graph convolutional network (RGCN). Experiments on both IEEE 39 Bus and IEEE 300 Bus system verify the effectiveness of the proposed RGCN model for collective anomaly detection so as to ensure the stability of power grids.…”
Section: Collectivementioning
confidence: 99%
“…Despite the model's universality potential to cope with other networked industrial control systems, it has been found that this hybrid design can not detect unknown attack/fault types [114]. A novel Graph Neural Network (GNN) based framework, combining graph convolutional network (GCN) and LSTM model has been proposed for multi-task multi-task transient stability classification [115]. The hybrid design of GNN is found able to effectively analyze complex spatio-temporal patterns in the IEEE 39 Bus system and IEEE 300 Bus system [115].…”
Section: H Hybrid Models-basedmentioning
confidence: 99%
“…A novel Graph Neural Network (GNN) based framework, combining graph convolutional network (GCN) and LSTM model has been proposed for multi-task multi-task transient stability classification [115]. The hybrid design of GNN is found able to effectively analyze complex spatio-temporal patterns in the IEEE 39 Bus system and IEEE 300 Bus system [115]. The fly in the ointment is that the GNN-based models require [116].…”
Section: H Hybrid Models-basedmentioning
confidence: 99%
See 1 more Smart Citation
“…GT explores the relationship between the structural properties and the eigenvalues and eigenvectors of the corresponding matrices [11]. GT has been widely applied in various areas, including data analysis [11]- [13], communication [14], [15], traffic networks [16], [17], and energy networks [18], [19]. Typically, GT represents a network in a mathematical graph as G = G(V, E), where V denotes vertices (e.g., demand nodes, reservoirs, and tanks in a WDN) with n elements, and E represents edges (e.g., pipes, pumps, and valves in a WDN) with m elements [5].…”
Section: Introductionmentioning
confidence: 99%